Weak magnetism and pseudoscalar coupling in neutrino mass mechanism of neutrinoless double beta-decay - Pantis, G.; Simkovic, F. (HNPS Advances in Nuclear Physics, 2019)
In the calculations of the nuclear matrix element of Majorana neutrino mass mechanism of neutrinoless double beta decay so far only contributions from vector/axialvector part and weak magnetism of the nuclear current have been included, while other contributions have been neglected. In the present work we are examining the effect of weak magnetism and induced pseudoscalar coupling. We have performed calculations within the proton-neutron renormaiized quasiparticie random phase approximation and we have found that these additional contributions of the nucleon current, result in a considerable reduction of the nuclear matrix elements of all nuclei which we have considered. This reduction of the nuclear matrix element makes the extracted limits of the lepton number violating parameters ( < mu >, < g > and < 77^ >) less stringent yielding the best value for < mv > less than 0.62 eV for 76Ge.